2010
DOI: 10.1007/s00467-010-1641-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of nephropathic cystinosis: a 20-year single-center experience

Abstract: Nephropathic cystinosis (NC) is a severe disease that is complicated by early-onset chronic renal failure (CRF) and other complications related to cystine deposition in tissue. Since the 1980s, the prognosis of NC has dramatically improved after the introduction of cysteamine treatment. Limited data are available documenting improvement in prognosis. We reviewed our long-term data (follow-up 6.3-27.8 years) on 23 patients followed in the past 26 years. Overall, stage III CRF was reached at 10 years of age in >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 36 publications
4
51
3
3
Order By: Relevance
“…Finally, no information was available on those starting RRT beyond the age of 20 years. Nevertheless, the mean age of onset of RRT in our cohort (12.8 years) was slightly higher compared with that recently reported from Australia and New Zealand (12.3 years in 2008) (26) and was comparable with that recently reported from a single center in Italy (8).…”
Section: Increased Age At Start Of Rrt In Nc Patientssupporting
confidence: 52%
See 2 more Smart Citations
“…Finally, no information was available on those starting RRT beyond the age of 20 years. Nevertheless, the mean age of onset of RRT in our cohort (12.8 years) was slightly higher compared with that recently reported from Australia and New Zealand (12.3 years in 2008) (26) and was comparable with that recently reported from a single center in Italy (8).…”
Section: Increased Age At Start Of Rrt In Nc Patientssupporting
confidence: 52%
“…A recent observational study from Italy suggested a positive effect of angiotensin-converting enzyme (ACE) inhibitors on renal function survival in patients with NC (8). Unfortunately, we could not evaluate the role of ACE inhibitors or any other supportive therapies because these data were not available.…”
Section: Increased Age At Start Of Rrt In Nc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective data analyses have demonstrated that kidney functional decline, and perhaps other organ functions, can be delayed and sustained, respectively, when a biomarker of the efficacy of cystine depletion, white blood cell (WBC) cystine, is ,2 nmol 1/2 cystine/mg protein (11,12). There have been no prospective trials with Cystagon for the therapy of cystinosis.…”
Section: Introductionmentioning
confidence: 99%
“…Before the availability of cysteamine, most patients with nephropathic cystinosis developed ESRD within the first decade of life. 9,10 Its efficacy as a renoprotective agent in nephropathic cystinosis is well established, yet the specific protective mechanisms remain incompletely understood. There is no question that cysteamine dramatically lowers intracellular levels of cytotoxic cystine, but this effect alone does not fully explain its renoprotective effects and led us to consider an alternative mechanism of action.…”
mentioning
confidence: 99%